CASUAL FACTROS OF CRIMINAL BEHAVIOR IN PUNJAB, PAKISTAN - Syed Muzaffar Hussain shah; Saralah Devi Mariamdaran; Rana Zafar Iqbal; Mohan a/l Rathakrishnan; Saria Aleem (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2018)
This study was conducted to find out the casual factors of criminal behavior in, Punjab Pakistan. Punjab is the largest province of Pakistan and crime ratio is also highest in this province. A questionnaire of 114 items was constructed through focus group discussion, Literature and DSM-5. Five point Likert scale was used to measure the casual factors. Data was collected from 200 criminals who conducted the crime more than one time. Data was collected from District jails of Multan and Vehari from south Punjab. Mean value was selected as 2 for mentioning a factors as cause of criminal behavior which indicate the presence of a factor. In last 20 factors were mentioned as casual factors of criminal behavior including physical abuse in schools, stubbornness in childhood, feelings of hopelessness and helplessness in childhood, strict family restrictions in childhood. Failure in intimate relations, high media exposure, short temperament, feelings of revenge and deprivation in childhood. Most of the criminals found to get their primary and secondary education in schools whereas there were lowest ratio of criminals who get religious education. There is needed to make policies to reduce these casual factors to control crime in Pakistan. Key Words: Crime, Criminal Behavior, Criminal Tendency, Criminal Factors, Causes of Crime.